2023
DOI: 10.1007/s00415-023-11888-8
|View full text |Cite
|
Sign up to set email alerts
|

Presymptomatic geographical distribution of ALS patients suggests the involvement of environmental factors in the disease pathogenesis

Rosario Vasta,
S. Callegaro,
S. Sgambetterra
et al.

Abstract: Background Given that the pathogenetic process of ALS begins many years prior to its clinical onset, examining patients’ residential histories may offer insights on the disease risk factors. Here, we analyzed the spatial distribution of a large ALS cohort in the 50 years preceding the disease onset. Methods Data from the PARALS register were used. A spatial cluster analysis was performed at the time of disease onset and at 1-year intervals up to 50 years p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…There are weaker or conflicting data for other putative environmental risk factors [ 1 ]. Nevertheless, a recent study on the geographical distribution of presymptomatic ALS patients revealed higher-incidence cluster areas, supporting the idea that exogenous factors may be involved in the ALS pathogenesis [ 86 ]. This hypothesis is in line with the results of another recent study focused on ALS incidence among immigrants in Sweden, which found that the risk of ALS was the same as native Swedish only in second-generation individuals, while it was lower in first-generation people [ 87 ].…”
Section: Environmental Factorsmentioning
confidence: 83%
“…There are weaker or conflicting data for other putative environmental risk factors [ 1 ]. Nevertheless, a recent study on the geographical distribution of presymptomatic ALS patients revealed higher-incidence cluster areas, supporting the idea that exogenous factors may be involved in the ALS pathogenesis [ 86 ]. This hypothesis is in line with the results of another recent study focused on ALS incidence among immigrants in Sweden, which found that the risk of ALS was the same as native Swedish only in second-generation individuals, while it was lower in first-generation people [ 87 ].…”
Section: Environmental Factorsmentioning
confidence: 83%
“…Finally, we compare the geochemistry at the different hATTR clusters and attempt to find common features that could be related to hATTR pathogenesis. It has previously been argued that some neurodegenerative diseases could be related to metal exposure [14][15][16][17], possibly of geochemical origin [18,19]. Here, we investigate and discuss if such metal exposure could be a potential contributing factor for hATTR onset.…”
Section: Methodsmentioning
confidence: 94%
“…Even though significant progress has been made in understanding-and treating-hATTR at the molecular level, the mechanism of pathogenesis and the overall origin of the disease remain unclear [12,13]. It has previously been argued that some neurodegenerative diseases could be related to metal exposure [14][15][16][17], possibly of geochemical origin [18,19]. Here, we investigate and discuss if such metal exposure could be a potential contributing factor for hATTR onset.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Finally, we discuss the known environmental risk factors and highlight how they participate in protein aggregation and their relevance to copper and protein aggregation. This is a key point as much of the cause of SALS appears to be environmental, as demonstrated by hotspots of increased ALS incidence or ALS risk-associated occupations in many countries ( Caller et al, 2009 ; Henry et al, 2015 ; Goutman et al, 2022 ; Vasta et al, 2023 ). In this regard the most notable risk factors seem to be related with contamination of food or water sources with plant and algal toxins, and also heavy metals ( Newell et al, 2022 ), all of which either enhance protein aggregation or interact with copper or cuproproteins in a detrimental manner ( Dunlop et al, 2013 ; Jaishankar et al, 2014 ; Sheykhansari et al, 2018 ; Balali-Mood et al, 2021 ; Diaz-parga et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%